Radicalism unveiled - Wali, Farhaan (Religion and international security, 2013)
Radicalism Unveiled is an essential and unique contribution to our knowledge concerning the rise of Islamic radicalism in Britain. Through the study of Hizb ut-Tahrir (The Liberation Party), the author shows that Muslim youth in Britain are increasingly linked to this group and that the spectre of radicalisation remains relatively unchallenged within British society. By penetrating the clandestine veil of Islamic radicalism, this book is able to interpret and analyse the closed social world of radical activism and help determine and explain why some young Muslims join Hizb ut-Tahrir.